Oficina De Criatividade Sonora: Concepts About Music, Images and Sounds in a Collaborative Experimental Podcast in Northern Brazil - Heitor Martins Oliveira; Leonardo Luigi Perotto (INSAM)
What is sound experience? How does it relate to our interpretation and perception of art and daily life? Oficina de Criatividade Sonora – Sound Creativity Workshop – is a collaborative experimental podcast created by composer Heitor Martins Oliveira, from Brazil, in order to generate online content and interact with his students, other artists, and the community, during the global pandemic of 2020. Musician and visual artist Leonardo Luigi Perotto joined as a close collaborator. Every week, from April to June, they released an image/score on social media and received audio files – created and sent mostly via smartphones – from followers. The audio – including singing, talking, instruments, and soundscapes – was edited by Oliveira to create sound compositions or narratives. Some contributors were asked to comment on their reading of the scores. The weekly podcast episodes featured commentaries and the resulting sound experiment. Since contributors are free to interpret the images/scores, they construct their own criteria and structural principles for sound creation. Their choices are related with their life experiences in music, other arts, or any other fields. These sound experiments reveal how contributors think about images and their relation to sound and music, their cultural, political and educational significance.